Clinical Presentation, Management and Outcome of adult congenital heart disease at tertiary care hospital in Pakistan - Aliya Kemal Ahsan; Usman Tauseef; Muhammad Ayyaz; Abdul Sattar Shaikh (Pakistan Journal of Medical Sciences, 2026)
Objective: To evaluate the clinical presentation, management and outcomes of adult congenital heart disease (ACHD). Methodology: This cross-sectional study was conducted at the department of pediatric cardiology and Intensive Care Unit (ICU) of NICVD, Karachi, Pakistan, from April 2021 to December 2023. Patients of either gender, aged 18 years and above and diagnosed with CHDs were analyzed. Outcomes were noted in the form of intra-operative or post-surgery mortality, and post-surgical complications. Results: In a total of 129 patients, 68 (52.7%) were male. The median age was 22.00 years. There were 10 (7.8%) ACHD cases who were newly diagnosed. The most common CHD types were found to be tetralogy of Fallot (TOF), atrial septal defect (ASD), and ventricular septal defect (VSD), noted in 32 (24.8%), 25 (19.4%), and 22 (17.1%) patients, respectively. Shortness of breath, cyanosis, and palpitation, were the most frequent complaints at the time of presentation, reported in 120 (93.0%), 48 (37.2%), and 44 (34.1%) patients, respectively. Cardiac catheterization was the most adopted procedure performed in 41 (31.8%) patients. Total correction, VSD closure, and ASD closure were performed in 9 (7.0%), 7 (5.4%), and 7 (5.4%) patients, respectively. No intra-operative or post-operative mortality was reported. The most frequently observed post-operative complications were left ventricular dysfunction, right ventricular dysfunction, biventricular dysfunction, and hypertrophic cardiomyopathy, noted in 39 (30.2%), 23 (17.9%), 6 (4.7%), and 3 (2.3%) patients, respectively. Conclusion: The most prevalent ACHD types were TOF, ASD, and VSD. Most patients required surgical or catheter-based interventions with favorable short-term outcomes.